Karakterizacija lesnih spojin v tehnološki vodi iz proizvodnje lesovine - Zule, Janja (Les (Ljubljana), 2002)
Problems, caused by accumulation of different wood components in papermaking process waters, are indicated. Analytical procedure for chemical characterization of predominant dissolved and colloidal substances is described. Process water samples from the production o mixed softwood mechanical pulp have been systematically analyzed. Types and concentrations of monosaccharide units from soluble hemicelluloses have been identified and quantitatively evaluated, as well as amounts of various wood extractives and polymer lignin.
Keywords: lesovina; tehnološke vode; kemijska analiza